Endogienous Nitrogen and Amino Nco Secretions in Monogastric Animals - A Review (Journal of Science and Technology, 2016)
The characterization and measurement of endogenous ileal nitrogen and amino acid excretion of simple-stomached animals, including pigs and poultry, is important to an understanding of gastro-intestinal physiology, as having practical application in the determination of amino acid requirements by the factorial method and the determination of dietary true amino acid digestibility. Studies indicate that the amount of endogenous nitrogen entering the mammalian gastro-intestinal tract is considerable.Traditionally, the net endogenous loss of protein from the ileum has been determined by feeding animals a protein-free diet, although the regression technique has been applied also. However, the protein-free method may lead to considerable underestimation of the physiologically normal level of endogenous excretion. The regression technique seems to give rise to endogenous loss values similar to those obtained after feeding animals to a protein-free diet and therefore the use of this approach may also lead to error. Moreover, the homarginine (guanidination) method in which intact protein is given to the animal, allows direct measurement only for the endogenous loss of lysine. An alternative and more general approach is the isotope (either a radioactively labelled amino acid or the stable isotobe; 15N) dilution method. Central to this method is choice of a suitable precursor pool for the endogenous nitrogen-containing material. However, because the nature and origin of these nitrogen-containing compounds is not fully resolved, it is not possible to specify a precursor pool with confidence. A new method for determining endogenous ileal amino acid excretion that involves feeding the animal peptides followed by ultrafiltration of the ileal digesta, has been proposed and evaluated. The enzyme hydrolysed protein approach is not subject to the criticisms of the protein-free or regression methods. Given the unphysiological nature of protein-free dietary state and the problems associated with the other methods, the enzyme hydrolysed protein method may give rise to more meaningful estimates of basal endogenous nitrogen and amino acid tools.